ANTESEDEN DAN KONSEKUENSI DARI PERCEIVED SERVICE RECOVERY - Adrian Nugroho; Luki Adiati Pratomo (Prosiding Seminar Nasional Pakar, 2019)
This study aims to examine the effect of Involvement, Expectations, Fear ofrelationship loss, Feedback and Forgiveness on Perceived Service Recovery,and the influence of Perceived service recovery on Satisfaction.The researchdesign used is hypothesis testing research. The sample used was 293respondents who used a mobile provider for more than one year, hadexperienced service failure and had received service recovery from the provider.The sampling technique used was purposive sampling. The results show thatExpectations, Fear of relationship loss, Feedback, Forgiveness have positiveinfluences on Perceived Service Recovery but Involvement did not, andPerceived Service Recovery has a positiveimpact on Satisfaction.